Peluang dan Tantangan Anak Berkebutuhan Khusus (ABK) Terhadap Implementasi Kebijakan Inklusi di Indonesia - Rusly, Muhammad; Bramuda, Anggun C Dmas Putri (Journal of Innovation in Teaching and Instructional Media, 2024)
The community's response to inclusive education is highly positive, reflected in the increasing number of schools implementing it and a significant rise in student enrollment. However, the implementation of inclusive policies in Indonesia has yet to meet expectations. This article utilizes a library research method aimed at reviewing relevant sources regarding opportunities and challenges for ABK in the implementation of inclusive policies in Indonesia. The results obtained are diverse, influenced by cultural differences, traditions, and implementation at the provincial, municipal, and school levels, from early PAUD to higher education. Opportunities include positive changes in ABK, the fulfillment of the objectives of the UU as guidance for the Education Department in implementing inclusive education, and the acceptance of ABK within the community. Meanwhile, challenges include the lack of experience among GPK, budget constraints, and inadequate standard facilities in some schools.